Syphilis response policies and their assessments: A scoping review - Almeida, Milena C. D.; Cordeiro, António M. R.; Cunha-Oliveira, Aliete; Barros, Daniele M. S.; Santos, Diana G. S. M.; Lima, Thaísa S.; Valentim, Ricardo A. M. (Frontiers in Public Health, 2022)
Syphilis is one of the most common sexually transmitted infections (STIs) worldwide and has shown a rising trend in recent years, according to a report published by the World Health Organization (WHO) in 2021. Given this problem, the present study aims to develop a scoping review of what has been done in the world after the publication of the global strategy for the elimination of STIs, with a specific focus on syphilis. Thus, we searched for papers on health policies in response to syphilis in Pubmed, Scopus, ScienceDirect, and EBSCO by CINAHL, as well as in official documents from international health organizations. The period from January 1, 2016, to August 14, 2022 was considered. Our search returned 880 papers addressing “Syphilis,” “Health Policy,” and “Health Policies” combined. Twenty-three papers fulfilled the inclusion and exclusion criteria according to two research questions set out for this scoping review. Our findings suggest that Brazil and Peru presented the greatest adequacy of the strategies provided by WHO in 2016 and the Pan American Health Organization (PAHO) in 2017, aiming tothe goals set out in the UN's 2030 Agenda for sustainable development. Among the studies found, six countries (Cuba, Thailand, Belarus, Armenia, Moldova, and Puerto Rico) reported the elimination of mother-to-child transmission (MTCT) of syphilis, but the most recent data are from 2016. Furthermore, it is essential to mention that no country has been found that has presented a comprehensive response to syphilis, noting the control or elimination of the disease in all key populations. Thus, it is necessary to constantly monitor national policies based on in-depth studies on the quality of the response, the challenges, and the national, regional, and global perspectives for the control of the disease until 2030, the year in which the SDGs will be reviewed. Systematic review registration https://osf.io/x9er5/?view_only=0cc0062222ec45dcb2f4d41484d285b6, identifier: 10.17605/OSF.IO/X9ER5.